ACCESS TO JUSTICE AND DEVELOPMENT IN PERSPECTIVE: AN ANALYSIS OF PROTECTION AND ASSISTANCE TO VICTIMS OF TRAFFICKING IN PERSONS IN MOZAMBIQUE - José Nhatave, Guirino Dinis; Cuco, Arcénio Francisco; da Silva Frota, Francisco Horácio (Revista Inclusiones, 2021)
Within the framework of protection of victims of trafficking in persons described in Chapter II of the Additional Protocol to the United Nations Convention against Transnational Organized Crime on the Prevention, Suppression and Punishment of Trafficking in Persons, in particular Women and Children (Protocol of Palermo [2000]) victims of trafficking in persons are entitled to assistance and protection. It is a set of measures that aim to guarantee their access to justice and create conditions for them to have a dignified and safe return in their communities, guaranteeing them protection rights (medical, psychological and material assistance), as well as creation employment, education and training opportunities. Taking these elements into account, this work seeks to understand how victims of trafficking in persons have access to justice and mechanisms that allow them an adequate social reintegration, taking into account their post-rescue vulnerability. The thesis of the article is that in Mozambique there are legal conditions for access to justice given the existence of criminal legislation for the accountability of offenders, as well as the provision of specific legal measures for the protection and assistance to victims. However, there are difficulties for the social reintegration of victims since there are no concrete programs for this purpose and institutional conditions for monitoring them. The work is bibliographical and documentary in nature. It uses documents prepared by the United Nations (conventions, treaties and official documents) and Mozambican legislation on human trafficking to assess the framework formulated for victims' access to justice and the consequent guarantee of their rights. The article concluded that, for victims of trafficking in persons, conditions of protection and assistance must be created that allow them to develop economically in order to reduce their vulnerability to trafficking